2014
DOI: 10.1016/j.jfa.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the degenerate principal series on symmetric R -spaces and small representations

Abstract: Let G be a simple real Lie group with maximal parabolic subgroup P whose nilradical is abelian. Then X = G/P is called a symmetric R-space.We study the degenerate principal series representations of G on C ∞ (X) in the case where P is not conjugate to its opposite parabolic. We find the points of reducibility, the composition series and all unitarizable constituents. Among the unitarizable constituents we identify some small representations having as associated variety the minimal nilpotent K C -orbit in p * C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…For P and P conjugate this is shown in [11,Corollary 2.32]. For P and P not conjugate we showed in [21,Theorem 5.3 (2)] that the associated variety of J(ν 1 ) is the minimal nilpotent K C -orbit. Since the Joseph ideal is the unique completely prime ideal in U (g) with associated variety the minimal nilpotent K C -orbit, it remains to show that the annihilator ideal of J(ν 1 ) is completely prime.…”
Section: Nowmentioning
confidence: 59%
See 2 more Smart Citations
“…For P and P conjugate this is shown in [11,Corollary 2.32]. For P and P not conjugate we showed in [21,Theorem 5.3 (2)] that the associated variety of J(ν 1 ) is the minimal nilpotent K C -orbit. Since the Joseph ideal is the unique completely prime ideal in U (g) with associated variety the minimal nilpotent K C -orbit, it remains to show that the annihilator ideal of J(ν 1 ) is completely prime.…”
Section: Nowmentioning
confidence: 59%
“…In many cases these operators can be obtained from standard families of intertwining operators such as the Knapp-Stein intertwiners. However, as observed in [21] in the case where P and P are not conjugate such families do not exist. Still, unitarizable quotients can occur in this setting, and hence the corresponding intertwiners cannot be obtained from standard families by regularization.…”
Section: 4mentioning
confidence: 83%
See 1 more Smart Citation
“…[11,Corollary 2.4.3 & 2.5.8]). In [24,Theorem 5.3] we showed that the unitary principal series representations π iλ,k attain the minimal possible Gelfand-Kirillov dimension among all infinite-dimensional unitary irreducible representations of G. (In fact, we only showed the statement for k = 0, but the proof carries over to the case k ∈ Z. )…”
Section: Unitary Principal Series Representationsmentioning
confidence: 94%
“…Let π t,k := Ind G P (χ t,k ) denote the corresponding unitary principal series representations (normalized parabolic induction). The structure of these representations was studied by Dooley-Zhang [4] (see also [11,24]). For t = iλ ∈ iR and k ∈ Z the representation π t,k is unitary and irreducible and called unitary principal series representation.…”
Section: Unitary Principal Series Representationsmentioning
confidence: 99%